2008
DOI: 10.1634/stemcells.2007-0885
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by Retroviral Vectors of Bone Marrow-Derived Mesenchymal Cells Induces Mitochondria-Dependent cAMP-Sensitive Reactive Oxygen Species Production

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Piccoli et al (2008) demonstrated increased reactive oxygen species production in engineered BM-MSC due to regularly used selection markers. Expression of neomycin or puromycin resistance genes resulted in oxidative stress.…”
Section: Genetically Engineered Msc For Gene Directed Enzyme Prodrug mentioning
confidence: 99%
“…Piccoli et al (2008) demonstrated increased reactive oxygen species production in engineered BM-MSC due to regularly used selection markers. Expression of neomycin or puromycin resistance genes resulted in oxidative stress.…”
Section: Genetically Engineered Msc For Gene Directed Enzyme Prodrug mentioning
confidence: 99%
“…One possibility for viral induced redox perturbations was suggested by Piccoli et al [14]. They suggested that the overexpression of the antibiotic selection genes, Neo-R and PAC for LXSN and pQCXIP respectively are responsible for a decrease in mitochondrial electron transport chain Complex I functionality, and the subsequent increase in ROS [14].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed decreased cAMP concentration in the kidney tissue after endotoxemia and it was preserved by an infusion of amrinone. An increased tissue cAMP level has been shown to protect against hypoxemia induced endothelial injury by preserving endothelial barrier function [5], to improve post-ischemic recovery in the liver and kidney [6,7], and to regulate mitochondrial function [28,29]. Increasing cAMP attenuates iNOS expression [30].…”
Section: Discussionmentioning
confidence: 99%